1951
DOI: 10.1097/00000658-195110000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Pump-Oxygenator to Replace the Heart and Lungs; An Apparatus Applicable to Human Patients, and Application to One Case*

Abstract: The authors hereby express their most appreciative recognition of the contribution of our machinist, Mr. Hilbert Huso, without whom the present machine could not have been constructed. They also wish to express gratitude to Miss La-Vonne Young and Miss Donna Nissen, technicians, and to Mr. titc'iard Kelly, a pre-medical student helper, who have volunteered uncounted extra hours to the prosecution of this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0
5

Year Published

1954
1954
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 1 publication
0
42
0
5
Order By: Relevance
“…Unfortunately, follow-up studies indicated that 30% to 40% of the patients remained uncured, as judged by hemodynamic measurements. The reasons for this are twofold: (1) incomplete or inac¬ curate division of the pulmonary valve; (2) failure to recognize or to be able to correct associated defects (infundibular stenosis, or atrial or ventricular septal defects).…”
Section: Tetralogy Of Fallotmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, follow-up studies indicated that 30% to 40% of the patients remained uncured, as judged by hemodynamic measurements. The reasons for this are twofold: (1) incomplete or inac¬ curate division of the pulmonary valve; (2) failure to recognize or to be able to correct associated defects (infundibular stenosis, or atrial or ventricular septal defects).…”
Section: Tetralogy Of Fallotmentioning
confidence: 99%
“…A clinical application of his type of pump-oxygenator, as modified by Dennis,2 was attempted at the University of Minnesota in 1951. Both operations were for an atrial septal defect, and were unsuccessful.…”
mentioning
confidence: 99%
“…Examinations within the scope of organ perfusion [4][5][6][7], the discovery of blood groups [8], and the clarification of heparin's effects on blood clotting [9] led to the development of heart-lung machines which maintained blood flow using membrane pumps [10,11 ], roller pumps [12,13,14] or centrifugal pumps [15].…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite this early failure, the use of CPB has grown to become an important technique used for nearly 750 000 open-heart surgical procedures annually around the world. There have been many improvements in heart-lung machines, blood pumps, oxygenators, perfusion circuitry, filtration, safety devices, and monitoring devices.…”
mentioning
confidence: 99%